Compositional inhomogeneity and tuneable thermal expansion in mixed-metal ZIF-8 analogues. Issue 69 (13th August 2018) - Sapnik, Adam F.; Geddes, Harry S.; Reynolds, Emily M.; Yeung, Hamish H.-M.; Goodwin, Andrew L.
Abstract : We study the structural and thermomechanical effects of cation substitution in the compositional family of metal–organic frameworks Zn1− x Cd x (mIm)2 (HmIm = 2-methylimidazole). Abstract : We study the structural and thermomechanical effects of cation substitution in the compositional family of metal–organic frameworks Zn1− x Cd x (mIm)2 (HmIm = 2-methylimidazole). We find complete miscibility for all compositions x, with evidence of inhomogeneous distributions of Cd and Zn that in turn affect framework aperture characteristics. Using variable-temperature X-ray powder diffraction measurements, we show that Cd substitution drives a threefold reduction in the magnitude of thermal expansion behaviour. We interpret this effect in terms of an increased density of negative thermal expansion modes in the more flexible Cd-rich frameworks.